INVESTASI REKSA DANA SAHAM SECARA JANGKA PANJANG DI INDONESIA BERDASARKAN KEPUTUSAN KETUA BAPEPAM - LK - Reinandus Aditya Gunawan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
Decision of Head of BAPEPAM dan LK Nr: Kep-176/BL/2008 provided that investment manager is restricted to do equity buying at company stock which listed in Bursa Efek Indonesia more than 5 % of the said company. This regulation has effected to mutual fund, so the said mutual fund cannot put into the long term investment because they can’t make a decision based on the ownership of the stock less than 5%. This regulation made the mutual fund manager do the day trading strategy on their investment becaused they can’t invest for the long term. Day trading strategy has made the stock market index (in Indonesia called Indeks Harga Saham Gabungan /IHSG) susceptible for the stock market crash. So investor should invest in hedge funds, private equity funds, or protected mutual fund which has long term investment policy.